Schwann cell plasticity regulates neuroblastic tumor cell differentiation via epidermal growth factor-like protein 8 - Tamara Weiss (Nature Portfolio, 2021)
Schwann cells (SCs) can acquire a repair phenotype following nerve injury. Here, the authors show that stromal SCs in ganglioneuromas express nerve-repair genes. Importantly, neuroblastoma cells respond to repair-related SCs increasing neuronal differentiation and reducing proliferation via EGFL8.